2011
DOI: 10.1590/s0102-33062011000400009
|View full text |Cite
|
Sign up to set email alerts
|

Variação sazonal dos grupos funcionais fitoplanctônicos em braços de um reservatório tropical de usos múltiplos no estado de São Paulo (Brasil)

Abstract: A análise dos grupos funcionais fitoplanctônicos em sistemas aquáticos pode oferecer subsídios à conciliação dos usos múltiplos. Essa pesquisa investigou a variação sazonal desses grupos no reservatório de Itupararanga (SP). Quatro braços foram amostrados para determinação de temperatura da água, pH, Radiação Solar Fotossinteticamente Ativa Subaquática (RSFA), turbidez, fósforo total, nitrato e sólidos suspensos totais (SST), além da contagem e identificação do fitoplâncton e análise de dados meteorológicos. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 37 publications
4
20
0
4
Order By: Relevance
“…Positive correlation between pH and phytoplankton has also been found in studies of Dantas et al (2008) and Cunha and Calijuri (2011). The seasonal variation of pH can be explained by the increased consumption of CO 2 during the summer (Palma et al 2010).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Positive correlation between pH and phytoplankton has also been found in studies of Dantas et al (2008) and Cunha and Calijuri (2011). The seasonal variation of pH can be explained by the increased consumption of CO 2 during the summer (Palma et al 2010).…”
Section: Discussionmentioning
confidence: 60%
“…Inverse relationships between transparency of water and biomass of phytoplankton have been reported (Moura et al 2007b, Chellapa et al 2009, Costa et al 2009, Cunha and Calijuri 2011. Some works indicate a dominance of P. agardhii in periods with less luminosity and higher turbidity (Chellapa et al 2009, Kokocinski et al 2010, 2012.…”
Section: Discussionmentioning
confidence: 96%
“…In Brazil, studies on phytoplankton in short sampling intervals (24 hours cycle) have been carried out with his approach (Araújo et al, 2000;Barbosa, 2002;Melo and Huszar, 2000;Nabout and Nogueira, 2007;Becker et al, 2009;Barbosa et al, 2011;Cunha and Calijuri, 2011;Cruz, 2011;Dantas et al, 2009;Dantas et al, 2011). Natural coastal lagoons in Rio Grande do Norte systems are important, especially when using as water supply for the city of Natal, as in Extremoz Lake (Raposo and Gurgel, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, the low similarity suggests that the Itupararanga Reservoir is a heterogeneous ecosystem supporting the growth of different species contributing to biological diversity. Despite the low spatial variation of the physical and chemical variables, some recent studies (Cunha & Calijuri, 2011b;Bottino et al, 2013) reported that the main factors related to the spatial heterogeneity of ) at different sampling sites of the Itupararanga Reservoir in two seasons (summer and winter) in 2010. There were no measurements in the sampling sites with absence of macrophytes (in the winter P6, P7 and P9).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that an increase in nutrients is common during this period in the study area (Cunha & Calijuri, 2011b) and that the electrical conductivity may be considered an indirect measure of the concentrations of nutrients dissolved in the water (Cometti et al, 2008), an increase in this variable in the winter allowed us to suppose that the trophic status influenced the biomass of E. crassipes in the winter.…”
Section: Discussionmentioning
confidence: 99%